Central Banks and Monetary Regimes in Emerging Countries: Theoretical and Empirical Analysis of Latin America - Resende, Marco Flavio Cunha; Pereira, Wallace; Libânio, Gilberto (Brazilian Keynesian Review, 2024)
Resenha de livro